Pendampingan dalam Pembelajaran Al-Quran pada Anak-Anak Desa Sempu, Kecamatan Ngebel, Kabupaten Ponorogo - Laila Amalia Putri; Ibnu Muchlis (Social Science Academic, 2025)
The Community Service Program (Kuliah Pengabdian Masyarakat/KPM) is one of the manifestations of the Tri Dharma of Higher Education, emphasizing community engagement and service. This article aims to describe the strategies employed by KPM students to overcome the challenges of Qur’an learning among children in Sempu Village, Ngebel Subdistrict, Ponorogo Regency. This study employed a descriptive qualitative approach with a participatory model. Data were collected through observation, interviews with local Qur’an teachers, and documentation during the program. The subjects were eight children, consisting of two who were already reading the Qur’an and six who were still at the Iqra stage. The findings reveal significant improvements in children’s Qur’anic learning. First, their mastery of tajwid improved, particularly in applying rules of elongation and specific recitation laws. Second, the clarity of makhraj al-huruf (points of articulation) increased after intensive talaqqi practice. Third, children’s ability to write Arabic letters became neater and more accurate through step-by-step exercises. Fourth, children showed greater enthusiasm for learning, supported by stronger parental involvement. Furthermore, interviews with the Qur’an teacher highlighted limitations in time and energy for providing intensive guidance, yet acknowledged that the presence of KPM students was very helpful as motivators and technical assistants. The teacher also expressed the need for continuity after the program ends. In conclusion, the strategies of learning by doing and talaqqi were effective in improving Qur’anic learning among children in Sempu Village. The success of the program was supported by the dual role of KPM students as facilitators and motivators, and by collaborative efforts among students, teachers, and parents. This research applies the Participatory Action Research (PAR) approach, which links research activities with processes of social change. The data were collected through field visits, interviews, observations, and analytical procedures.